Unlocking Green Patterns: The Local and Spatial Impacts of Green Finance on Urban Green Total Factor Productivity - Xiang, Jiyou; Tan, Linfang; Gao, Da (Sustainability, 2024)
The urgency of global climate change and environmental degradation has become increasingly apparent, and green finance, as a pioneering financial tool, is providing critical support to unlock regional green patterns. Based on the data of China’s prefecture level from 2010 to 2021, this study examines the causal relationship and mechanism of green finance (GF) and urban green total factor productivity (GTFP) using the spatial Durbin model. The results show the following: (1) Green finance can not only improve local GTFP, but also has a spatial spillover effect, and it is still valid after a robustness test, which means that the development of GF can significantly promote urban green transformation. (2) The local effect and spatial spillover effect of green finance are more obvious in coastal and developed areas. (3) After deconstructing the mechanism of green transformation, this paper finds that improving urban energy utilization efficiency, mitigating the capital mismatch degree, and enhancing new quality productivity are important impact channels for green finance to enhance urban GTFP. These conclusions not only provide a theoretical reference for GF to help with the construction of a high-quality “Double Cycle” new development pattern, but also promote low-carbon transformation. This study has obvious application value and provides experience for other developing countries to seek green transformation from the perspective of green finance practice.